Influence of Bituminous Layer Modulus and Soil Layer Properties on the Modulus of Granular Layer - Gopal, Sivaprakash; Padmarekha, Ajithkumar (Journal of Engineering and Technological Sciences, 2024)
Bituminous pavements are designed to withstand vertical compressive strain at the top of the subgrade layer and horizontal tensile strain at the bottom of the bituminous layer. The modulus value of all the layers acts as an important parameter for accurate pavement designing. As the value of the granular layer’s modulus is a function of deviatoric stress and confinement pressure, this research studied the influence of bituminous and soil layer properties on the modulus of the granular layer hypothesized to follow E = k1 θ^(k2 ), where θ represents the stress invariant and k1 and k2 denote constants. The granular layer modulus was predicted at different depths for various cases using the KENPAVE software. When the bituminous layer modulus was increased, the granular layer modulus decreased. When the bituminous layer thickness was smaller, the granular layer modulus decreased with depth. Increasing the thickness of the bituminous layer by 10 cm decreased its modulus by 10 MPa. Increasing the depth caused a decrease in the modulus of the granular layer, but the modulus of the subgrade had no effect. The trends of stresses and strains from the nonlinear analysis were identical to those of stresses and strains from the linear analysis.